Motor Seizures Confer Overall Survival Benefit in WHO Grade 2 Glioma. (1st October 2022) - Fairclough, Sam; Mathew, Ryan; Goodden, John; Chumas, Paul; Maguire, Melissa
Abstract: AIMS: The prevalence of epilepsy in WHO grade 2 glioma is high, with seizures often being the presenting symptom. We explore the epidemiology of seizures in this patient population in a regional neurosurgical centre. METHOD: Electronic health records of patients with histologically-proven WHO grade 2 glioma (n=227) were reviewed with data collected including patient demographics, epilepsy prevalence and seizure semiology. Relationships between epilepsy and overall survival were calculated using a Cox proportional hazards model in the statistical software "R, " controlling for all other variables – including histological diagnosis. RESULTS: Overall, 196/227 (86.3%) patients were diagnosed with epilepsy - either at presentation (179/196, 91.3%), or during the course of their disease (17/196, 8.7%) . Mean follow-up was 7.0 years. Diffuse astrocytoma histology was associated with reduced overall 10-year survival (HR 4.68, p<0.001) compared with oligodendroglioma. The majority of patients experienced focal onset seizures (n=118) as their predominant seizure type, with generalised (n=64) and unknown onset seizures (n=14) less likely. Almost two-thirds (64.8%) of those with epilepsy had experienced at least one generalised tonic-clonic seizure. During seizures, loss of awareness (n=132) and presence of motor activity (n=147) were frequently encountered. Predominantly experiencing seizures without any motor activity also appeared to confer poorer survival outcomes (HR 2.39, p<0.05), even when controlled for histology. CONCLUSION: Most WHO Grade 2 glioma patients experience focal seizures, though generalised tonic-clonic seizures are common. Motor seizure activity is a frequent feature in WHO Grade 2 glioma and may confer a survival benefit, when compared to patients that have primarily non-motor seizure activity.